Kontestasi Politik dalam Kompetisi Olahraga Ganefo - Harjo, Indhar Wahyu Wira (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2023)
This research examines the Games of New Emerging Forces (GANEFO) as a tactical sporting event. This review aims to show that Ganefo is not just an international sports competition, but is also a product of domestic political competition and diplomatic relations contests. This research uses historical research methods. The implementation of Ganefo in November 1963 is often associated with international political practices after World War II. The feud between the Western Bloc and the Eastern Bloc triggered the holding of the Asia-Africa Conference. It was the spirit of the Non-Aligned Movement that Indonesia adopted to mobilize other countries to participate in GANEFO. Apart from that, the influence of the PRC as an exponent of the communist state also played an important role in Ganefo's success in Jakarta. At the national level, the long feud between Soekarno, political parties and the military elite also contributed to the implementation of Ganefo during the Guided Democracy era. The competition between domestic camps was a trigger for Soekarno to try to take a superior position by holding international scale sporting events. Soekarno used this method to attract public sympathy as well as dwarf the position of his domestic competitors. Thus, holding sports competitions can be used as an instrument to unravel the complexity of diplomatic relations and domestic political contestation.